Implementasi Pembelajaran Daring Berbasis Project Dalam Pengembangan Digital Skill Melalui Program Studi Independen Di PT Revolusi Cita Edukasi - Bernadeth Gabriella Putri Hardianti; Jojok Dwiridotjahjono (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
In the current digital era, learning in the development of digital skills is very necessary for students to prepare for future careers. This learning can be done through the Merdeka Campus program, one of which is the Independent Study program. Therefore, this writing aims to provide an overview of the implementation of learning in the development of digital skills at PT Revolusi Cita Edukasi so that participants have a view of career opportunities that can be pursued in the digital era. The learning implementation method in this program is carried out online with asynchronous and synchronous activity types. This program is divided into 4 learning modules, namely Digital Marketing, Data Analytics, Product Management, and Software Engineering where participants are required to work on a capstone project in groups as the final project of each learning module and a means to build a portfolio. Therefore, the implementation of project-based learning at PT Revolusi Cita Edukasi can be the basis and reference if you want to go deeper into the field of interest so that you can have a career in that field.